Ultrasonic welding of fully and hybrid thermoplastic composite structures - Chua, Vincent Werlin (Nanyang Technological University, 2022)
Composite structures have been becoming increasingly popular in multiple industries such as the automotive, marine and aerospace sectors, due to its ability to be lightweight yet retaining its specific stiffness properties. Moreover, thermoplastics have been highly preferred due its resin having the ability to become softer once heated, while retaining its properties after cooling down. This makes them the perfect candidate for the ultrasonic welding joining method. Not only does ultrasonic welding provide excellent bonding between joints, it is also cost and time effective compared to other joining processes. Elium® is a novel acrylic thermoplastic resin that was utilized in this project, a first of its kind resin that that is able to cure at room temperature.